Cerebral peduncle angle: Unreliable in differentiating progressive supranuclear palsy from other neurodegenerative diseases. (November 2016) - Tipton, Philip W.; Konno, Takuya; Broderick, Daniel F.; Dickson, Dennis W.; Wszolek, Zbigniew K.
Abstract: Introduction: The significant symptom overlap between progressive supranuclear palsy (PSP) and other parkinsonian neurodegenerative diseases frequently results in misdiagnosis. However, neuroimaging can be used to quantify disease-related morphological changes and specific markers. The cerebral peduncle angle (CPA) has been shown to differentiate clinically diagnosed PSP from other parkinsonian diseases but this result has yet to be confirmed in autopsy-proven disease. Methods: Magnetic resonance imaging (MRI) scans were obtained for 168 patients representing 69 medical facilities. Following randomization, the images were divided into two groups (Type 1 and Type 2) based upon midbrain morphological differences. Two readers were blinded and independently measured the CPA of 146 patients with autopsy-proven progressive supranuclear palsy (PSP; n = 54), corticobasal degeneration (n = 16), multiple system atrophy (MSA; n = 11) and Lewy body disease (n = 65). Results: Applying two separate measurement techniques revealed no statistically significant differences in CPA measurements among any study groups regardless of classification measurement approach. The interobserver agreement showed significant differences in measurements using the Type 2 approach. Conclusion: Measuring the CPA on MRI is not a reliable way of differentiating among patients with PSP, corticobasal degeneration, MSA, or Lewy body disease. Highlights: There is variability in cerebral peduncular morphology on non-standardized MRI. Two techniques for measuring the CPA are proposed to address this variability. The CPA is not reliable in differentiating PSP from other parkinsonian-like diseases.